"Quadripolar" Transcranial Electrical Stimulation for Motor Evoked Potentials. Issue 1 (January 2022) - Schwartz, Stephanie L.; Kale, Emily B.; Madden, Dennis; Husain, Aatif M.
Abstract : Purpose: To determine if transcranial electrical stimulation (TES)–induced motor evoked potentials (MEPs) are of higher amplitude when using two electrodes as anodes and two as cathodes, known as "quadripolar stimulation." Methods: Patients who underwent TES MEP monitoring in which control, bipolar stimulation and four variations of quadripolar stimulation were used were evaluated. The bipolar stimulation montage was C3-C4 (C3 was used as anode for stimulation first, then the polarity was switched to stimulate the contralateral side). Four quadripolar montages were used: C3/C1-C4/C2 (step 1), M3/M1-M4/M2 (step 2), C3/M1-C4/M2 (step 3), and M3/C1-M4/C2 (step 4). The area under the curve for the right foot TES MEP was compared for the various montages using descriptive statistics and Fisher exact test for proportions. Results: Sixteen patients were retrospectively evaluated. The mean age as 51.6 years, range 4 to 80 years; 11 were female. The transcranial electrical stimulation MEP area under the curve for the right foot MEP was highest in the bipolar montage in 1 of 16 patients (6.3%). Meanwhile, it was highest in step 4 (M3/C1-M4/C2) in 9 of 16 patients (56.3%; P = 0.027). The highest right foot MEP area under the curve with one of the quadripolar montages was seen in 15 of 16 patients (93.8%; P = 0.0001). Conclusions: Quadripolar stimulation resulted in higher area under the curve for right foot MEP compared with conventional bipolar stimulation.